EKSPLORASI TUMBUHAN PAKU PADA BEBERAPA HABITAT DI KABUPATEN MANOKWARI, PROVINSI PAPUA BARAT - Susanto, Slamet Arif; Lefaan, Paskalina Theresia; Sutarno, Simon; Miftanti, Mar'ah (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2025)
Exploration studies of ferns in Papua Indonesia are still limited, while habitat pressure is increasing due to massive development. The purpose of this study was to quickly explore potential habitats of ferns in several areas in Manokwari Regency, West Papua Province. Direct observation methods and fern collections were carried out without observation plots. The ferns collected were unique and rare ferns. Samples from the collection were then carefully observed and made into sketches to facilitate the description process. Taking research location points and measuring environmental parameters were also carried out in areas where ferns were found. The results of the study showed that there was a diversity of habitat types, environmental conditions and how ferns grew. 10 types of ferns were found from four observation locations. The ten ferns were Psilotum nudum, Psilotum complanatum, Microsorum diversifolium, Nephrolepis biserrata, Blechnum orientale, Lycopodium cernuum, Lycopodium phlegmaria, Selaginella wildenowii, Stenochlaena palustris, and Lygodium microphyllum. Rare species tend to be less abundant, while cosmopolitan and potentially invasive species are very abundant. Literature studies show that more than 80% of the fern species that have been successfully inventoried have the potential to be medicinal plants. Based on the results of this initial study, quantitative ecological studies and bioprospection of ferns in Manokwari, West Papua still need to be carried out as an effort to conserve ferns Keywords: habitat exploration; Psilotum; Lycopodium; fern bioprospecting